O ENSINO DA GEOMETRIA PARA ALUNOS COM DEFICIÊNCIA VISUAL - Silva, Davi Cezar da (2013)
The present research aimed to promote inclusive education in math classes, investigate how the materials, which were developed and built by the researcher, helped a student with a visual impairment in mental imagery in relation to models of plane figures and spatial . Characterized as a case study, the research has qualitative character and it had as participant, a student with visual impairments distinguished as having blindness. From a literature review, which involved different authors, we seek to organize a survey that addressed beyond the history that involves inclusive education, present also the difficulties faced by teachers, students and schools facing this reality. The materials developed were all built with inexpensive materials and adaptations for students with visual impairment. The activities were elaborated to work primarily models of plane geometry figures and later relate, properties and concepts, with models of figures of spatial geometry. We noticed during the implementation of activities, beyond the motivation that brings a teaching resource to a student with Special Educational Needs, the materials developed by the researcher were of utmost importance and effectiveness for the student to understand the connections between the properties of figures in the plane and space geometries. Through reports the student was evident filling some gaps that still exist in their knowledge in relation to such content, for example, basic differences between pyramids and prisms with triangular bases, or between squares and cubes. As product of the dissertation professional, beyond the material itself, was elaborated a videoaula available on DVD-ROM and on the website of the Course of Master Professional in Teaching Physics and Mathematics UNIFRA.